THEMATIC FIELD SCHOOL OF SHALLOT COMMODITY AS AN AGRICULTUREAL EXTENSION METHODE TO IMPROVE FARMERS, KNOWLEDGE, ATTITUDES, SKILLS AND PRODUCTIVITY - Rahyunanto, Setyo; Sepfrian, Bimoseno (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Extension agriculture have important role? for development source Power man agriculture in development agriculture that aims For increase knowledge , attitude , skills And product activity results . Various method extension Already implemented in activity the including school roomy thematic based? approach participatory . Study This aim For know school roomy thematic commodities shallot as method counseling agriculture For increase knowledge , attitude , skills And productivity result . Method study is qualitative descriptive . Informant on study This a total of 30 farmers participant school field . Results study show that school roomy thematic commodities shallot cause a number of matter namely , farmers shallot show category very agree that school roomy increase knowledge And previous skills? they Not yet understand or know . In improvement attitude And productivity results , showing category agree . Recommendation results study is implementation extension agriculture based on participatory with method school roomy thematic more developed again with adapt need farmer .